2017
DOI: 10.5152/eurjbiol.2017.1713
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis and Antimicrobial Effect of Propolis from Hakkari Province of Turkey against Some Pathogenic Microorganisms

Abstract: This study was performed to investigate the antimicrobial effect of propolis from Hakkari province of Turkey and its chemical content by Gas Chromatography-Mass Spectroscopy. In vitro inhibitory activity of propolis was studied by the disc diffusion method against six gram positive, three gram negative bacteria and one yeast like fungi. As a result of chemical analysis, the total flavonoid ratio of the propolis sample was found to be higher than the other compound groups. Pinostrobin chalcone, pinocembrin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Moreover, Bayram et al. (2017) worked on different samples from Chile and Spain on the same bacterial strains. It is evident from the present study that gram‐positive bacteria were more sensitive to Chinese propolis extract, as shown in Table 2 ( RHP : Listeria monocytogenes 21.58 ± 3.6 mm > Staphylococcus aureus 17.12 ± 0.91 mm > Bacillus subtilis 16.05 ± 0.54 mm > E.coli 0 YHP : Listeria monocytogenes 18.95 ± 0.16 mm > Staphylococcus aureus 18.27 ± 0.25 mm > Bacillus subtilis 15.07 ± 0.11 mm E.coli 0; LSP Listeria monocytogenes 16.77 ± 1.02 mm > Staphylococcus aureus 15.40 ± 0.54 mm > Bacillus subtilis 16.33 ± 1.03 mm > E.coli 0; CHP Listeria monocytogenes 17.70 ± 0.75 mm > Staphylococcus aureus 15.27 ± 0.16 mm > Bacillus subtilis 16.67 ± 0.65 mm > E. coli 0 ) , so Chinese propolis has very little or no effect on gram‐negative bacteria ( E. coli ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Bayram et al. (2017) worked on different samples from Chile and Spain on the same bacterial strains. It is evident from the present study that gram‐positive bacteria were more sensitive to Chinese propolis extract, as shown in Table 2 ( RHP : Listeria monocytogenes 21.58 ± 3.6 mm > Staphylococcus aureus 17.12 ± 0.91 mm > Bacillus subtilis 16.05 ± 0.54 mm > E.coli 0 YHP : Listeria monocytogenes 18.95 ± 0.16 mm > Staphylococcus aureus 18.27 ± 0.25 mm > Bacillus subtilis 15.07 ± 0.11 mm E.coli 0; LSP Listeria monocytogenes 16.77 ± 1.02 mm > Staphylococcus aureus 15.40 ± 0.54 mm > Bacillus subtilis 16.33 ± 1.03 mm > E.coli 0; CHP Listeria monocytogenes 17.70 ± 0.75 mm > Staphylococcus aureus 15.27 ± 0.16 mm > Bacillus subtilis 16.67 ± 0.65 mm > E. coli 0 ) , so Chinese propolis has very little or no effect on gram‐negative bacteria ( E. coli ).…”
Section: Resultsmentioning
confidence: 99%
“…These assays are mainly spectrophotometric, which include free radical scavenging (Pobiega et al., 2019), ferric reducing antioxidant power (Ahmed et al., 2017; Gülçin et al., 2010), and electrochemical methods (Rebiai et al, 2011). A lot of results have described the antimicrobial and antibacterial activity of propolis extracts, noting that phenolic compounds, terpenoids and nonaromatic acids are primarily responsible for the inhibiting microorganism growth (Bayram et al., 2017; Martinotti & Ranzato, 2015; Yuan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that propolis has antioxidant, antimicrobial, antiparasitic [5], antiviral, anti-inflammatory [6,7], and anticancer [8] properties. A recent study also proved that propolis has antitoxic and antimutagenic activities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Propolis is well known for its diverse and beneficial biological effects such as antibacterial (Bayram et al, 2017, Temiz et al 2011), antifungal (Silici et al 2005), anti-Inflammatory (Kolaylı et al 2016, and antioxidant (Temizer et al, 2017). It is also known to stimulate wound healing, reduce tumefaction and suppresses pain (Zilius et al 2016).…”
Section: Introductionmentioning
confidence: 99%